Nihilent technologies: recommending change at the banking : recommending change at the Banking Association South Africa. (A) - Metton, Eulalie; Rijamampianina, Rasoava ([London] : SAGE, 2016)
In September 2008 Ravi Teja, associate vice president and head of enterprise transformation at the global consulting company, Nihilent, reviewed progress on the Banking Association South Africa project. Nihilent's analysis of the situation clearly showed that there was a need to restructure the organisation and that an effective performance management system should be put in place to enable it to achieve its objectives. The challenge was how to do this without unnecessarily alienating Banking Association employees, and this was one of the key points on the agenda.
Originally Published in: Metton, E. & Rijamampianina, R. (2010). Nihilent: Recommending Change at The Banking Association South Africa (Part A). WBS-2010-5. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Banking Association South Africa; Employees -- Rating of -- Case studies; Corporate turnarounds -- Case studies; Organizational change -- Case studies